2018
DOI: 10.1371/journal.pone.0201537
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate control in reducing FGF23 levels in hemodialysis patients

Abstract: BackgroundIn hemodialysis patients, high levels of Fibroblast Growth Factor 23 (FGF23) predict mortality. Our study was designed to test whether the control of serum phosphate is associated with a reduction in serum FGF23 levels. Additionally other variables with a potential effect on FGF23 levels were evaluated.Material and methodsThe effect of sustained (40-weeks) control of serum phosphate on FGF23 levels (intact and c-terminal) was evaluated in 21 stable hemodialysis patients that were not receiving calcim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…For instance, intravenous iron administration, which was not accounted for in this analysis, increases intact FGF23 among dialysis patients independent of serum calcium and phosphorus levels [20,21]. Long-term control of serum phosphorus with non-calcium based phosphate binders may result in decreases in FGF23 levels [22,23], while active vitamin D stimulates FGF23 production [24]. Our study did not account for changes in serum phosphorus, type of phosphate binder, or prescription of active vitamin D; however, low baseline serum phosphorus and no baseline use of active vitamin D analogues were strongly associated with the low stable FGF23 trajectory.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…For instance, intravenous iron administration, which was not accounted for in this analysis, increases intact FGF23 among dialysis patients independent of serum calcium and phosphorus levels [20,21]. Long-term control of serum phosphorus with non-calcium based phosphate binders may result in decreases in FGF23 levels [22,23], while active vitamin D stimulates FGF23 production [24]. Our study did not account for changes in serum phosphorus, type of phosphate binder, or prescription of active vitamin D; however, low baseline serum phosphorus and no baseline use of active vitamin D analogues were strongly associated with the low stable FGF23 trajectory.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Serum FGF23 concentrations have been shown to correlate positively with serum phosphate levels [41]. Recent study showed that the control of serum phosphate could reduce FGF23 levels [42]. From our results, it showed that CharXgen and AST-120 were capable of binding phosphate in conditions such as in small and the large intestine.…”
Section: Discussionmentioning
confidence: 51%
“…One notable problem is that some patients were probably in a state of phosphate overload, albeit within normal limits. Fibroblast growth factor 23 (FGF23) is increased in the early stages of CKD, even before phosphate retention occurs, and is more suitable to be considered an indicator of phosphate overload [19]. Thus, further studies including the assessment of FGF23 are needed to evaluate the relationship between serum phosphorus and KSD before optimal reference ranges are developed to guide clinical practice.…”
Section: Homa2-ir (>1)mentioning
confidence: 99%